Solar radiation modelling and measurement techniques in Lafia Zone, Nasarawa state, Nigeria - Mamman, Andah; Ibrahim, Umaru; M. Idris, Mustapha; A. Mundi, Abdullahi; U. Sarki, Musa (EDUCATUM Journal of Science, Mathematics and Technology, 2020)
The number of solar radiations measuring stations in Nigeria has been observed not to effectively describe the necessary variability; as such prediction models are necessary for estimation of solar radiation values using readily available meteorological variables. In this study, solar radiation parameters were determined for Lafia zone, Nasarawa State, Nigeria. Twelve (12) location were carefully selected to avoid sunshine and wind obstruction using a systematic random sampling technique. Three-hour daily measurement (12.00 pm to 2.00 pm) was done on three 12V, 5W solar panels using a pyranometer and the output was estimated using the Angstrom-Prescott Regression Equation. The continuity in the assembled system was measured using an Avometer. The result revealed that solar radiation intensity was found to range from 165.5 W/m2 to 298.6W/m2 with the mean value of 241.24 W/m2.The highest global solar radiation value of 29.8MJ/m2was observed in April while the lowest value of 16.5MJ/m2was observed in August. The extraterrestrial solar radiation was found to range from 9.06 MJ/m2 in August to 26.60 MJ/m2 in February with average value of 20.96MJ/m2. The atmospheric transmission coefficient over the year is found to range from 0.7 in July and September to 1.4 in December. The obtained atmospheric transmission coefficient determined for the year (2019) is a good indication for solar radiation application in Lafia geo-political zone, Nasarawa State. The performance of the developed model is observed to imply that it can be used to predict global solar radiation for Lafia zone in Nasarawa State.